2010
DOI: 10.4038/cmj.v49i4.1919
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for neonatal hypoglycaemia in Kerala, India

Abstract: Objectives To detect the incidence and risk factors that predicted the occurrence of neonatal hypoglycaemia and to identify neonates who require mandatory blood glucose screening during the first 48 h of life.Design Hospital based prospective study in a maternity centre in south India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 13 publications
9
40
2
Order By: Relevance
“…In addition to this they found that breast feeding delay of greater than 2 hours and maternal oligihydraminos after delivery considerably increases the risk of neonatal hypoglycemia. 13 The overall incidence of asymptomatic hypoglycemia was in the present study was found to be 20%. Diwakar et al in their study of healthy term infants found out the incidence to be 14%.…”
Section: Discussionsupporting
confidence: 46%
“…In addition to this they found that breast feeding delay of greater than 2 hours and maternal oligihydraminos after delivery considerably increases the risk of neonatal hypoglycemia. 13 The overall incidence of asymptomatic hypoglycemia was in the present study was found to be 20%. Diwakar et al in their study of healthy term infants found out the incidence to be 14%.…”
Section: Discussionsupporting
confidence: 46%
“…Preterm infants are especially vulnerable. Hypothermia is also associated with serious morbidities, such as increased risk of IVH, 19,26,39,[50][51][52][53][54] respiratory issues, 15,19,21,50,[55][56][57][58][59][60] hypoglycemia, 15,44,[60][61][62][63][64] and late-onset sepsis. 33,65 Because of this, admission temperature should be recorded as a predictor of outcomes as well as a quality indicator (Class I, LOE B-NR.)…”
Section: Importance Of Maintaining Normal Temperature In the Deliverymentioning
confidence: 99%
“…43,60 For the serious outcome of hypoglycemia, there were seven observational studies (very-low-quality, downgraded for risk of bias and indirectness) showing a significant association between hypothermia (less than 36°C) and hypoglycemia. 44,67,70,[97][98][99][100] Two of these studies, using historical controls, showed improved glycemic control with improved normothermia. 44,99 For the serious outcome of late sepsis, 2 observational studies (very-lowquality evidence, downgraded for risk of bias and indirectness) indicated an association between hypothermia on admission and late sepsis.…”
Section: Consensus On Sciencementioning
confidence: 99%